Primary Cesarean Rates at a Community Hospital: Differences Between Residency and Private Practice [15J]. (May 2018) - Quinn, Shantel; Butz, Anh; Simpson, Barbara; Stovall, Dale W.
Abstract : INTRODUCTION: Reducing cesarean delivery rates remains a primary objective in obstetrics. Differences in labor management and practice environment likely contribute to variation in the rate of cesarean delivery. This research compares the rate of primary cesarean delivery of an obstetrics & gynecology residency and a private practice at the same community hospital. METHODS: In this retrospective cohort study, all deliveries over an 18-month period were reviewed. Demographic information including age, race, gravidity/parity, gestational age, pregnancy complications, maternal comorbidities, and indication for cesarean delivery were obtained. RESULTS: The residency performed 1, 114 vaginal and 346 cesarean deliveries, for an overall cesarean rate of 23.7%. The private practice performed 1, 223 vaginal and 482 cesarean deliveries, for an overall cesarean rate of 28.3%. Considering only primary cesarean deliveries, the residency performed 188 cases (14.4%), while the private practice performed 271 cases (18.1%). The residency performed significantly fewer primary cesarean deliveries (P = 0.009) and had a significantly lower cesarean rate overall (P = 0.004). The cohorts differed significantly in age, gravidity/parity, and indication for cesarean delivery. Delivery was indicated most often by non-reassuring fetal status for the residency cohort (48.9%) and by labor dystocia (arrest of descent or dilation) for the private practice (38.0%) (P < 0.0001). Prevalence of hypertension, diabetes, and other comorbidities did not differ between cohorts. CONCLUSION: Residency practice patterns might yield lower cesarean delivery rates. Further study of differences in indication for cesarean and role of age and multiparity could help identify strategies to reduce primary cesarean delivery.